Risk of suicide in patients who present to hospital after self-cutting according to site of injury: findings from the Multicentre Study of Self-harm in England - Geulayov, G; Casey, D; Bale, E; Brand, F; Clements, C; Farooq, B; Kapur, N; Ness, J; Waters, K; Patel, A; Hawton, K (Cambridge University Press, 2021)
Background We compared the risk of death by suicide following hospital presentation for self-harm according to site of self-cut/stab.